Performance Evaluation of the Central Stores of Hospitals Affiliated to Tehran University of Medical Sciences in 2018 - zahra Tahmasebi; Maryam Tajvar; Mohammad Arab (Tehran University of Medical Sciences, 2019)
Background: Due to the presence of valuable and expensive equipments in hospitals' warehouses, scientific management and continuous evaluation plays an important role to improve the performance of warehouses and whereby the performance of hospitals' wards. This study aimed to evaluate the performance of the central stores of hospitals affiliated to Tehran University of Medical Sciences (TUMS). Materials and Methods: In order to conduct this cross-sectional study, a checklist was designed and validated to examine the warehouses' status considering structural, process and outcome dimensions of 39 depots in 14 hospitals. The status of hospitals' warehouses were assessed using descriptive analysis and in order to assess association between performance evaluation score and charchetristics of warehouses and its staff Pearson Correlation Coefficient was utilized. Results: Although, warehouses' performance of studied hospitals in general was satisfactory, there were some items in unsuitable condition particularly in structural and process dimensions which should be addressed quickly. Also, performance of warehouses revealed a positive and significant correlation with number of beds, area and size of warehouse and number of staff (p <0.05). Conclusion: Given that fair warehouses status, some items particularly in structural and process dimensions were in inappropriate condition which needed rapid consideration. Furthermore, hospitals with more beds have more and bigger warehouses achieved better evaluation score, but some of warehouses without these condition should be addressed in priority.